Erros de medicação em unidade de pronto atendimento - Lima, Edmila Lucas de (2018)
This is a descriptive study aimed at characterizing errors in prescribing, preparing and administering medications in the emergency room. The study involved all doses of injectable, prescribed, prepared and administered as well as the nursing professionals involved in the preparation and administration. Data collection took place over a period of 30 days in a care unit in the state of Goiás. It was performed in three stages: 1) Direct non-participant observation and registration of the information in a checklist during medication preparation and administration. 2) Record of prescription information in a validated and adapted checklist for this study; 3) Application of questionnaire to the professionals observed during the preparation and administration of the doses. The data was entered into an Excel worksheet and analyzed using descriptive statistics. The project was approved by the ethics committee of the Pontifical Catholic University of Goiás under No. 1822.751 and met all the ethical aspects of human research. A total of 751 doses were studied, 746 doses given and 753 doses were evaluated. The study was attended by 25 nursing professionals, most of them between the ages of 30 and 39 years and professional experience from 01 to 10 years. The most frequent errors in the prescribed doses were the use of abbreviated way, failure to define infusion speed and the use of nonmetric expressions. In the preparation, the main errors found were associated to antimicrobial protection measures: hand hygiene; disinfection of vials and jars. Most failures in relation to the doses administered were related to the information of the drug administered; identification of the patient and identification of drug allergy. We can conclude that errors are present in medical prescription, drug preparation and administration, and good practices regarding preparation and administration need to be reviewed as well as the development of human resource skills and competencies and infrastructure adequacy to ensure safety the use of drugs in emergency units.